Sources of Superior Performance: Market Share Versus Industry Effects in the U.S. Brewing Industry - Montgomery, Cynthia A.; Wernerfelt, Birger (Management Science, 1991)
Using financial measures of performance we investigate the sources of value creation in the U.S. brewing industry between 1969 and 1979. We find that market share gains in this industry at this time are not correlated with changes in value and that the performance of individual leading firms is highly correlated. Our interpretation is that the success of market share building strategies depends critically on specific industry conditions. Specifically, in the absence of fundamental shifts in the relative resource positions of individual firms, share gains may come at too high a price. In addition, the research shows that intra-industry correlations in returns may result from excessive competition rather than collusion.